Prática docente e formação discente: o caso da escola Eulalice Pinheiro de Miranda, Abaetetuba-PA - PIMENTEL, Hetiany da Silva (2019)
The objective of this study is to analyze the contribution of pedagogical pedagogical practice in the training of the students of the Antônia Eulalice Pinheiro de Miranda school, located in the community of Alto Guajará de Beja, PA 409 km 09, Abaetetuba-Pará municipality, through a case study in the sense of contributing to the improvement of this training. This research was carried out with the students of the 4th and 5th grades of elementary school, in order to improve the quality of the educational process of the students mentioned above. Therefore, this research is a case study of a qualitative nature, based on observations of the reality of the school experience. Thus, this work was developed from field research, conducted during the period from February to March 2019. Thus, I justify the research, due to the need to understand the pedagogical practice used in the school by the teaching staff, as well as the space in the same is inserted, that is, in the field, and still be able to contribute effectively to the improvement of the community. In this way, this research intends to know the teacher training and the pedagogical practice used in the school Antônia Eulalice Pinheiro, to know the methodology applied to the students, as well as the experience of the students of the 4th and 5th year, as well as the professionals who work in the school. The achievement of these objectives led to the production of a qualitative research, with observation, interview, confronting them with bibliographic studies. Field research was carried out at the elementary and elementary school Antônia Eulalice Pinheiro de Miranda located in the community of Alto Guajará de Beja PA 409, rural area of the city of Abaetetuba-PA. A total of 8 interviews were carried out, one with the school manager, one with the teacher of the 4th and 5th multisseries classes, and a focus group with six students in the class, three in the fourth grade and three in the 5th grade, chosen by the teacher.